Six Points a Legacy of Historic Events in Bangladesh: An Education Perspective - Ritesh Karmaker; Shamoly Malaker (Universitas Pendidikan Indonesia (UPI), 2023)
The article shows that Six-Point has been a prime political Impetus created by Bangabandhu Sheikh Mujibur Rahman, the father of the nation. In it, he has risen the importance of rights to be ensured for the people of Bengal who were deprived of their rights and struggling to lead a secure life and rightful position. This demand raised by Bangabandhu is a leading political issue that even smoothens the achievement of independence. Bangabandhu points out the demands after being deprived of the rights known as the Charter of Freedom. So, he raises the demands and gives the Bengalis a road to be walked for the rights of their liberty. These points are the first political achievement of Bengalis through the demands raised by Bangabandhu. In this article, a qualitative approach has been poured and the significance of Six-Point has been seen in gathering data from Sherpur, Bangladesh. The Six-Point Movement has whirled the spirit inside the mind of the Bengalis and led them to further achievement and independence. The Six Points paced up other movements until they gain their liberty. The necessity of such demand is very much required for the momentum of the Bengalis of East Pakistan then and Bangabandhu holds the reasons of the Six-Point Movement for giving Bengalis the rights becoming rightful for ensuring their deprived rights in the demands, Six-Point Movement.